LANDASAN TEOLOGIS PENDIDIKAN ISLAM DALAM AL-QUR'AN: ANALISIS KONSEPTUAL TENTANG NILAI-NILAI PENGETAHUAN, KEBIJAKSANAAN, DAN PERAN MANUSIA SEBAGAI KHALIFAH - Maulida Mujahidah; Sarwadi Sulisno (PT. Saha Kreasi Indonesia, 2025)
This study aims to examine the verses of the Qur'an that serve as the theological foundation of Islamic education, including QS. Al-Baqarah verse 269 and QS. Al-An'am verse 165. The research method used is a literature review (library research) and conceptual analysis of the verses of the Qur'an, by identifying, grouping, and analyzing key concepts in the Qur'an and establishing their implications for contemporary Islamic education. Through the analysis of these verses, it was found that Islamic education is not only oriented towards mastering knowledge, but also on the formation of character and spiritual awareness of humans as servants and caliphs of Allah on earth. Thus, this theological foundation provides direction for the implementation of Islamic education that is oriented towards the development of the whole person, including the dimensions of reason, faith, and charity.